Tension wiring to increase stability of conventional plating for proximal humeral fractures: An alternative to a locking plate - Kai-Lan Hsu; Ta-Wei Tai; Wei-Ren Su; Chii-Jeng Lin; Pei-Yuan Lee (Tzu Chi Medical Journal)
Fixation of comminuted or osteoporotic fractures in the proximal humerus is a challenge for orthopedic surgeons. In the past two decades, locking plates have been used for proximal humeral fracture fixation. However, complications such as loss of reduction have been reported, and the implants are not always available in some regions. Therefore, we describe an alternative procedure involving fixation with a nonlocking cloverleaf plate augmented with tension wiring to provide adequate stability and prevent loss of reduction.